Kits and their unique role in molecular biology: a brief retrospective. (April 2008) - Weiner, Michael P.; Slatko, Barton E.
An innovation is one of those things that society looks at and says, if we make this part of the way we live and work, it will change the way we live and work. — Dean Kamen One of my primary objects is to form the tools so the tools themselves shall fashion the work and give to every part its just proportion. — Eli Whitney It's what you learn after you know it all that counts. — Harry S. Truman Since their initial development nearly 20 years ago, molecular biology kits have evolved from simple protocols and reagents for cloning of DNA to the more recent complex reagent sets that enable whole genomic sequencing. Initially met with resistance by some who felt that using them deprived researchers of the basic knowledge of how to create reagents, molecular biology kits have taken on an important role in the biological sciences. In this article we describe kit development, why kits have succeeded in molecular biology, and how they have paved the way for the more recent widespread use of core facilities.